THE NATURE OF THE STATE BUDGET AND ITS ROLE IN THE SOCIO-ECONOMIC DEVELOPMENT OF THE COUNTRY - Yuldashev Asqarali Yakubovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article discusses some issues such as the formation of the role of the state budget in the socio-economic development of the country, as well as key factors.